Remembering Adibah Noor / Nazima Versav Kudus and Suzana Ab Rahim - Versav Kudus, Nazima; Ab Rahim, Suzana (Academy of Language Studies, 2022)
The demise of Adibah Noor on June 18, 2022 was a great shock to the nation. She was a multi-talented individual, held multiple roles during her lifetime - singer, actor, talent show judge and host (corporate events, television and radio). As a trained English language teacher and a public figure, she was never short of advice in the media on how good language should be used whether in the Malay or English language. She was never afraid to comment on the grammar, pronunciation and enunciation of a news anchor, minister and fellow entertainers. Adibah was a fellow TESL student, together with the authors, 35 years ago. Here, we would like to share some snippets of what kind of a person she was to us.